2014
DOI: 10.1016/j.semcdb.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β signaling to chromatin: How Smads regulate transcription during self-renewal and differentiation

Abstract: Ligands of the TGF-β superfamily (including the TGF-βs, Nodal and BMPs) play instructive roles during embryonic development. This is achieved by regulation of genes important for both maintaining pluripotency and germ layer specification and differentiation. Here we review how the TGF-β superfamily ligands signal to the chromatin to regulate transcription during development. The effectors of the pathway, the Smad transcription factors, are regulated in a combinatorial and spatiotemporal manner. This occurs via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 120 publications
1
119
0
1
Order By: Relevance
“…isoform of Smad2 does not (14). Here, we focused on Smad3 and generated a reporter C2C12 cell line stably expressing an mNeonGreen-Smad3 construct (NG-Smad3; the sequence is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…isoform of Smad2 does not (14). Here, we focused on Smad3 and generated a reporter C2C12 cell line stably expressing an mNeonGreen-Smad3 construct (NG-Smad3; the sequence is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in epidermal stem cells (Janich et al, 2011;Karpowicz et al, 2013) and the central clock (the suprachiasmatic nuclei; Beynon et al, 2009), a circadian pattern of TGF-b signaling activity as indicated by Smad3 phosphorylation has been reported. Given the importance of TGF-b signaling in stem cell proliferation and differentiation (Gaarenstroom and Hill, 2014), circadian modulation of this pathway might confer appropriate responses to temporal cues involved in controlling stem cell behavior and tissue homeostasis. Although our current study defines a specific role of Bmal1 in the brown fat differentiation program, its broader impact on various important TGF-b-regulated biological processes remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Smads can also integrate the input of FGF/RTK signalling, via MAPK-mediated phosphorylation, which can, for example, promote Smad1 degradation, and reduce BMP signal transduction [12,28]. Further information on how Smads integrate input from other signalling pathways can be found in other reviews [7,10,29].…”
Section: Introductionmentioning
confidence: 99%